AL-FARA’A SAYING IN THE PROVISIONS OF AL-MUSAQAT AND ALMAZRA’A, STUDY THROUGH THE BOOK ZAD AL-MUSTAQNI - Yaqdan Sami Muhammad Al-Jubouri; Ali Jamil Khalaf (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
od created the creation and belittled the earth to live it, and mocked them for what was in it. The relationship between man and those around him did not come in vain. Rather, it is the appreciation of God, the Glorious, the Knowledgeable. The observer finds in the provisions of the noble Sharia it has given great attention to the fields of investing natural resources, for this you find the Holy Prophet, may God’s prayers and peace be upon him, recommends cultivation and planting the land even if the caller calls for the establishment of the Hour. The Importance Of hence writing the On The mpeg Of Watering And Cultivation, So The idea A Of writing the Extensively Takes by most Judgments Of Hwy, And The Research Focused On The Jurisprudence by most important ’s related Friends To This Section In The important ’s Manner Of Investigation And Demonstration And According to the following structure: Preface: It includes a brief translation of the owner of the board of Alzad, the first topic: in the provisions of the course, and the second topic: in the provisions of agriculture, and the conclusion: and the most important results. Finally, we ask God Almighty to guide and reconcile.